The Development of IoT-Based Nutrient Mixing System for Hydroponic Fertigation - Trisna, I Made Andika Dwi; Sumiyati; Budisanjaya , I Putu Gede (Jurnal BETA (Biosistem dan Teknik Pertanian), 2022)
The development of IoT (Internet of Things) is an effort to unite the real world, the cyber world, and the social world has also been used in the agricultural sector, such as in hydroponic system. Proper nutrition requires a system that can assist farmersin providing the right nutrients concentration supported by technological developments with the help of sensors tomeasure them in the main tank. The purpose of this research is to develop IoT-based nutrient mixing system for hydroponic fertigation, that can provide nutrients in the form of dissolved AB Mix fertilizer according to the farmer needs via the internet remotely. The design in this research includes the use of Arduino Mega 2560 R3 as a microcontroller which is connected to the DS18B20 sensor as a temperature sensor, Keyestudio KS0429 sensors to measurenutrient concentration, relay as an applicator controller, the 16x2 LCD as a data display, NodeMCU Lolin V3 as a sender and data receiver on Google Firebase (database server) via the internet on a WiFi (Wireless Fidelity) network, as well as the user interface software for Android OS smartphone that can be usedby farmers to monitor the nutrient concentrations and determine the desired set point value. The system has successfully read, sent, received, and stored data with a fast internet connection over a WiFi network, the test result of the DS18B20 sensor with a strong correlation level of 0.89 and the Keyestudio KS0429 sensor of 0.8 with the Pearson method, and the result of overall prototype test with RMSE (Root Mean Square Error) value of 0.08 and time efficiency in providing nutrition is77.77%.